The Effect of Macroeconomic Factors on the Profitability of Non-Finance Firms in South Africa - Okofo-Dartey, Emmanuel (Acta Universitatis Danubius. Œconomica, 2024)
This study examines the effect of macroeconomic factors on the profitability of non-finance firms in South Africa. Using an annual dataset of listed non-finance firms from 2006 to 2022, and employing the Generalized Method of Moments technique results show that, prior profits of the firms positively influence their current profit levels. The study finds that, interest rates negatively affect the profit levels of the firms. Again, the result of the study reveals that while inflation, exchange rates, corporate tax rates, work ethics, and unemployment negatively influence profitability through Return on Assets (ROAs), they impact the profitability of the firms positively through Return on Equity (ROE). Corruption was also found to positively influence profitability through ROA but negatively through ROE. Policymakers are advised to monitor the effects of macroeconomic variables and assess the net effect of the volatility of these variables on the behaviour of non-financial firms in their respective economies to address the various dynamics posed by the macroeconomic factors to firms.